2022
DOI: 10.1158/1538-7445.am2022-2030
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2030: A single-cell spatially resolved map of colorectal cancer identifies novel spatial relationships between cancer cells and the microenvironment

Abstract: Understanding the tumor microenvironment (TME) requires more than just a catalog of cell types and gene programs. It is critical to see the spatial organization of the cells are and where they form multicellular interaction networks. Here we present a single-cell spatially resolved transcriptomic analysis of human mismatch repair deficient (MMRd) and proficient (MMRp) colorectal cancer (CRC) specimens. High tumor mutational burden MMRd tumors are known to have an immune response characterized by higher cytolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These findings have the potential to lead to the development of treatment strategies that are specific to each tumor subtype. [ 85 ]…”
Section: Tme Profiling Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have the potential to lead to the development of treatment strategies that are specific to each tumor subtype. [ 85 ]…”
Section: Tme Profiling Toolsmentioning
confidence: 99%
“…These findings have the potential to lead to the development of treatment strategies that are specific to each tumor subtype. [85] Building on these early ST techniques, NGS-based approaches, such as Visium's 10x Genomics spatial technology, boast an enhanced resolution of 55 microns, higher throughput, and increased sensitivity, allowing for genome-wide ST tissue profiling. [79,86,87] 10x Genomics' capacity to detect areas of abnormal gene expression allows for in-depth investigations into diseases associated with tissue function and structure and the identification of new biomarkers by linking gene expression data to the tissue footprint.…”
Section: Spatial Transcriptomicsmentioning
confidence: 99%
“…Using a 450-gene MERFISH panel, Price et al. reported a shift in immune spatial organization between the two tumour subtypes i.e., human mismatch repair deficient and proficient tumors, opening new avenues for tumour subtype-specific treatment strategies ( 34 ).…”
Section: St Techniquesmentioning
confidence: 99%
“…MERFISH allows profiling of up to tens of thousands of RNA species at subcellular resolution, with a maximum 1 cm 2 capture area of FF/FFPE tissues. Using a 450gene MERFISH panel, Price et al reported a shift in immune spatial organization between the two tumour subtypes i.e., human mismatch repair deficient and proficient tumors, opening new avenues for tumour subtype-specific treatment strategies (34).…”
Section: Imaging-based Techniquesmentioning
confidence: 99%